Analisis Transparency Berdasarkan Perspektif Islam HR. Bukhari : 1928 - Sukma Restina Pradipta; Sekar Langit Putri Waluyo; Mohamad Djasuli (CV. ITTC INDONESIA, 2022)
Quote meaning HR.Bukhari: 1928 is a leader must be transparent in governing. Transparency is one of the important principles in realizing Good Corporate Governance. Transparency in service has an important role in realizing Good Corporate Governance. By implementing good corporate governance, it is believed that the company is able to strengthen its competitive position in a sustainable manner, besides that the company can manage resources and risks that will be faced more efficiently and effectively. With the implementation of each of the principles of good corporate governance by the company, this is the beginning of the company forming a system, structure and culture within the company that is more adaptive to the changes that will occur in the company's environment. Islam itself, of course, also has a much more complete concept and always upholds good morals and piety to Allah SWT, which is certainly a wall not to fall into things that are not honest in accepting trust. With the principles of Islamic Good Corporate Governance, it is hoped that the principles of Good Corporate Governance in general can coexist with an Islamic perspective.